On the estimation of car driver profiles - Balomenos, Themis; Pertselakis, Minas; McMahon, Edelle; Tsapatsoulis, Nicolas (My University, 2004)
This paper describes a methodology for estimating car driver profiles in no-stationary contexts through the use of an adaptive resource allocation neural fuzzy system. It provides information on which variables need to be measured for this purpose and how the dynamic component of a driver’s profile can be estimated with the use of the proposed neurofuzzy structure. The proposed methodology has been validated through a series of well-designed experiments conducted, in cooperation, by psychologists, engineers and computer scientists, and undertaken in the framework of the IST ORESTEIA project (2001-2003).
Keywords: Driver profile; Predictive variables; Empirical estimation; Adaptive neural fuzzy systems